2016
DOI: 10.1002/jsfa.8177
|View full text |Cite
|
Sign up to set email alerts
|

Comparative community structure of archaea in rumen of buffaloes and cattle

Abstract: This study indicated that there is a substantial difference in community structure of ruminal methanogens of cattle and buffaloes. The study has also indicated that the percent of species-level operational taxonomic units shared between cattle and buffalo is very low, and thus host species-specific methane mitigation strategies need to be developed for cattle and buffaloes. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
3
12
1
Order By: Relevance
“…These ndings rea rm the previous reports on the dominance of Methanobrevibacter methanogens in cattle [39,40] and buffaloes [41,42]. A meta-analysis of archaeal 16S rRNA sequences available in GenBank [43] supports our results for the similar distribution of Methanobrevibacter in cattle and buffaloes. The higher abundance of Mbr.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These ndings rea rm the previous reports on the dominance of Methanobrevibacter methanogens in cattle [39,40] and buffaloes [41,42]. A meta-analysis of archaeal 16S rRNA sequences available in GenBank [43] supports our results for the similar distribution of Methanobrevibacter in cattle and buffaloes. The higher abundance of Mbr.…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicated that in spite of the small representation of Methanomassiliicoccales in the rumen archaeal community, they were more diversi ed in Indian ruminants than that of the New Zealand. A meta-analysis [43] strengthened our results on the higher abundance of Methanomassiliicoccales in cattle as compared to buffaloes. Though the methane producing ability of the Methanomassiliicoccales members has not yet been explored; their high relative abundance, i.e., up to 50% of the total rumen archaea [24,57], is a clear indication of their possible involvement in rumen methanogenesis.…”
Section: Discussionsupporting
confidence: 77%
“…Using a rumen-derived inoculum, which harbours high microbial hydrolytic activities, could reduce the pre-treatment costs in anaerobic digestion since there is little or no requirement to add hydrolytic enzymes [ 18 ]. The rumen contains a large number of microorganisms with enormous diversity, of which includes at least 50 bacterial genera (10 10 –10 11 cells ml −1 ), 25 genera of ciliate protozoa (10 4 –10 6 cells ml −1 ), 6 genera of fungi (10 3 –10 5 zoospores ml −1 ), 11 genera of methanogenic archaea (10 9 cells ml −1 ) and bacteriophages (10 8 –10 9 phages ml −1 ) [ 19 , 20 ]. Rumen microorganisms are naturally involved in the degradation of carbohydrates and lignocellulosic biomass to a variety of VFAs and OAs [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rumen contains a large number of microorganisms with enormous diversity. At least 50 bacterial genera (10 10 -10 11 cells ml -1 ), 25 genera of ciliate protozoa (10 4 -10 6 cells ml -1 ), 6 genera of fungi (10 3 -10 5 zoospores ml -1 ), 11 genera of methanogenic archaea (10 9 cells ml -1 ) and bacteriophages (10 8 -10 9 phages ml -1 ) are present in the rumen of ruminants (Cobellis et al, 2016;Paul et al, 2017). The microbial diversity composition also varies depending on the type of host and the environmental conditions, such as domestic or wild animals and their diets .…”
Section: Animal Gut or Rumen Microorganisms And Organic Acid Productionmentioning
confidence: 99%
“…Using a rumen-derived inoculum, which harbours high microbial hydrolytic activities, could reduce the pre-treatment costs in anaerobic digestion since there is little or no requirement to add hydrolytic enzymes (Thoetkiattikul et al, 2013). The rumen contains a large number of microorganisms with enormous diversity, of which includes at least 50 bacterial genera (10 10 -10 11 cells ml -1 ), 25 genera of ciliate protozoa (10 4 -10 6 cells ml -1 ), 6 genera of fungi (10 3 -10 5 zoospores ml -1 ), 11 genera of methanogenic archaea (10 9 cells ml -1 ) and bacteriophages (10 8 -10 9 phages ml -1 ) (Cobellis et al, 2016;Paul et al, 2017). Rumen microorganisms are naturally involved in the degradation of carbohydrates and lignocellulosic biomass to a variety of volatile fatty acids and organic acids (Yue et al, 2013).…”
Section: Introductionmentioning
confidence: 99%